Recent advances in understanding cognitive and behavioural alterations after early-in-life anaesthesia exposure and new mitigation/alternative strategies in preclinical studies. Issue 4 (August 2021) - Neudecker, Viola; Perez-Zoghbi, Jose F.; Brambrink, Ansgar M.
Abstract : Purpose of review: Long-term behavioural and cognitive impairments after exposure to general anaesthetics during infancy is an intensely investigated and controversial topic. Recent clinical studies with prospective assessments associate exposure with long-term behavioural alterations rather than cognitive impairments. This review aims to provide an understanding of the long-term cognitive impairments and behavioural alterations found in recent animal studies and to summarize latest advances in strategies to protect against anaesthesia-induced developmental neurotoxicity (AIDN). Recent findings: Preclinical studies, particularly those in nonhuman primates (NHPs), provide accumulating evidence that anaesthesia exposure during infancy is associated with long-term alterations in behaviour, but cognitive impairments are more controversial. Results from recent studies aiming to find mitigating strategies to reduce AIDN or to identify alternative anaesthetic agents include the co-administration of dexmedetomidine with the anaesthetic drugs or the alternative use of hypnotic neurosteroids without being harmful to the developing brain. Summary: Recent findings in animal studies with translational relevance support the proposed association between early-in-life anaesthesia exposure and long-term alterations in behaviour. Studies aiming to prevent AIDN are promising and need evaluation in the NHP model. The careful design of subsequent translational studies will be critical to advance the field forward towards safer anaesthesia exposure in children.